Standard handbook for solid and hazardous waste facility assessments - Sara, Martin N. (CRC PRESS / Washington, 1994)
This book is the result of many years of trying to evaluate the physical reality of ground-water flow in geologic materials. This text concentrates on practical aspects of hydrology and was designed as a working tool used to evaluate the heterogenities of subsurface units